Increased Understanding of Nahwu through Innovation in the Application of Direct Methods: Experimental Studies on Arabic Language Students - Afandi, Ahmad; Fadhlan, Muhammad; Fikri, Ahmad; Aziz, Mahbub Humaidi (Institut Agama Islam Negeri Curup, 2024)
The study aimed to explain the application of the Direct Method in Nahwu learning at the State University of Malang. It analyzed the supporting and inhibiting factors of the Direct Method in Nahwu learning at the State University of Malang and described student applications in Nahwu learning at the State University of Malang. This study used a descriptive design with a quantitative and qualitative approach to describe the application, supporting, and inhibiting factors of the Direct Method in Nahwu learning. The population in this study was the entire 5th-semester academic community (lecturers and students) of the Arabic language education study program, Faculty of Letters, State University of Malang. The sample in this study was selected using Purposive Sampling, with specific criteria for sampling. The model in this study was a student of the class of 2021 Arabic language education study program, Faculty of Letters, State University of Malang, who was taking the application Nahwu Tsanawi course. This lecturer taught the application Nahwu Tsanawi course. The results of this study showed that: 1) Student interest in learning Nahwu in the Arabic study program at the State University of Malang increased with the learning steps applied by lecturers, such as the delivery of themes, objectives, and learning materials by linking the new material to the previous material; 2) the innovation of the Direct Method used by teachers in Nahwu learning had a positive impact on students' understanding of Nahwu; 3) the use of the Direct Method in Nahwu learning was categorized as good, evidenced by the percentage of success reaching an average score of 83.3%; 4) the use of learning media by lecturers in Nahwu learning at the Arabic Language Education study program, State University of Malang, increased student interest in learning Nahwu. Based on the findings above, it is concluded that the innovation of the direct Method has a positive impact on students in learning Nahwu in the Arabic Language Study Program State University of Malang.